2021
DOI: 10.1021/acsomega.1c02463
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cerium Dioxide Nanoparticles by Gas/Liquid Pulsed Discharge Plasma in a Slug Flow Reactor

Abstract: Cerium dioxide (CeO 2 ) nanoparticles have gained immense attention owing to their use in various applications. Current synthesis methods for CeO 2 nanoparticles including hydrothermal and chemical precipitation are time-consuming and require chemical reagents. In order to shorten the reaction time and avoid the use of organic reagents, a new method for CeO 2 nanoparticles synthesis in a slug flow system by atmospheric-pressure pulsed discharge plasma was proposed, which provided an easy, efficient, and contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The dye decomposition rates of methylene blue under different pressures are listed in Table from which it can be observed that the rates were low. According to our previous study, the concentration of reactive species generated by plasma increases with an increase in the number of electrodes. Therefore, the number of electrodes was increased to seven, including three ground electrodes and four high-voltage electrodes (Figure b).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The dye decomposition rates of methylene blue under different pressures are listed in Table from which it can be observed that the rates were low. According to our previous study, the concentration of reactive species generated by plasma increases with an increase in the number of electrodes. Therefore, the number of electrodes was increased to seven, including three ground electrodes and four high-voltage electrodes (Figure b).…”
Section: Resultsmentioning
confidence: 72%
“…Stable plasma was produced when uniform bubbles flowed through the electrodes at a high voltage. This system provides an easy, continuous, and environmentally friendly process and has been applied successfully for the decomposition of methyl blue and synthesis of silver nanoparticles and cerium dioxide nanoparticles . However, this system has only been applied under atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows the mechanism of synthesizing starch-capped AgNPs using APDP in a slug flow system. When the gas/liquid is discharged in a pulsed plasma, chemically active substances with reducing properties are generated [ 9 ]. High-voltage electrons ionize argon molecules in a local high electric field to form argon radicals.…”
Section: Resultsmentioning
confidence: 99%
“…No organic solvent was used in the whole APDP synthesis process. Moreover, APDP is a fully controllable reaction, and low-temperature synthesis prevents chemical functional group changes in stabilizers [ 7 , 8 , 9 ]. The AgNPs were fabricated in a slug flow reactor system equipped with a non-equilibrium atmospheric-pressure plasma.…”
Section: Introductionmentioning
confidence: 99%